2012
DOI: 10.1371/journal.pone.0051369
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Monkeys (Macaca mulatta) Detect Rhythmic Groups in Music, but Not the Beat

Abstract: It was recently shown that rhythmic entrainment, long considered a human-specific mechanism, can be demonstrated in a selected group of bird species, and, somewhat surprisingly, not in more closely related species such as nonhuman primates. This observation supports the vocal learning hypothesis that suggests rhythmic entrainment to be a by-product of the vocal learning mechanisms that are shared by several bird and mammal species, including humans, but that are only weakly developed, or missing entirely, in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(128 citation statements)
references
References 29 publications
11
116
1
Order By: Relevance
“…Similar results were found in newborn infants, but unfortunately the stimuli used with infants confounded MMN responses to beat changes with a general response to a change in the number of instruments sounding [6], so future studies are needed with newborns in order to verify these results. Honing et al [60] also recorded ERPs from the scalp of macaque monkeys. This study demonstrated that an MMN-like ERP component could be measured in rhesus monkeys, both for pitch deviants and unexpected omissions from an isochronous tone sequence.…”
Section: Functional Imaging Of Beat Perception and Entrainment In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in newborn infants, but unfortunately the stimuli used with infants confounded MMN responses to beat changes with a general response to a change in the number of instruments sounding [6], so future studies are needed with newborns in order to verify these results. Honing et al [60] also recorded ERPs from the scalp of macaque monkeys. This study demonstrated that an MMN-like ERP component could be measured in rhesus monkeys, both for pitch deviants and unexpected omissions from an isochronous tone sequence.…”
Section: Functional Imaging Of Beat Perception and Entrainment In Humansmentioning
confidence: 99%
“…virtually any vertebrate species). Why is it that macaques, despite their many similarities with humans, apparently find it so difficult to predictively time their taps to a beat, and show no evidence for grouping events into metrical structures [7,60]? Why is it that the one chimpanzee (out of three tested) who shows any evidence at all for beat perception and synchronization only does so for a single preferred tempo, and does not generalize this behaviour to other tempos [132]?…”
Section: Implications For Computational Models Of Beat Inductionmentioning
confidence: 99%
“…To date, only a few species (vocal-learning birds and a sea lion) have been shown to be capable of 'Complex SMS' by synchronizing to the beat of more complex, musical stimuli, indicating a capacity to extract a beat from a complex auditory stimulus, and even to map flexibly to different motor outputs [66,69,76]. Evidence for hierarchical metrical perception or other aspects of rich BPS has not yet adequately been examined in nonhuman animals [77,78].…”
Section: Evolutionary Originsmentioning
confidence: 99%
“…They evaluate several brain imaging methods, including functional and electrophysiological techniques, for investigating the underlying mechanisms. The neurophysiology of rhythmic behaviour is also discussed, informed largely by recent findings in monkeys using direct intracortical [71] and non-invasive techniques [72].…”
Section: (D) Five Fundamental Constraints On Theories Of the Origins mentioning
confidence: 99%